Inhibitory and Bactericidal Effect of Aqueous Pepper Extract (Capsicum annum L.), Capsaicin, and Capsaicin Combination with Amoxicillin against Streptococcus pyogenes - Azadeh Notashfard1; Majid Nojavan Asghari1 (Journal of Medical Microbiology and Infectious Diseases)
Introduction: Streptococcus pyogenes remains a significant human pathogen responsible for a spectrum of infections, including severe invasive diseases such as streptococcal toxic shock syndrome, and serious post-infectious sequelae like acute rheumatic fever and glomerulonephritis. Considering the recognized antimicrobial properties of Capsicum annuum L. (C. annuum L.) and the persistent clinical challenge presented by S. pyogenes, this study investigated the in vitro antimicrobial activity of an aqueous extract of Capsicum annuum L., Capsaicin (C₁₈H₂₇NO₃), amoxicillin, and a combination of Capsaicin with amoxicillin against S. pyogenes (ATCC 19615). The primary objective was to evaluate both the inhibitory and bactericidal effects of these agents, specifically exploring the potential for synergistic or additive interactions between a plant-derived compound and a conventional antibiotic to improve therapeutic potential. Methods: The antimicrobial activities were evaluated using broth microdilution to determine the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). Time-kill kinetics were assessed spectrophotometrically by monitoring bacterial growth. Additionally, disk diffusion assays were performed to evaluate antimicrobial susceptibility. Statistical analyses were conducted using one-way analysis of variance (ANOVA), followed by Tukey’s post hoc test to determine significant differences between treatment groups. Results: The aqueous extract of C. annuum L. and Capsaicin both demonstrated significant in vitro inhibitory and bactericidal activity against S. pyogenes. Specifically, MIC and MBC of the aqueous extract were determined to be 12 mg/mL and 14 mg/mL, respectively. For Capsaicin, the MIC was 15 μg/mL, and the MBC was 20 μg/mL. Consistent with these findings, disk diffusion assays revealed distinct zones of inhibition for both agents. Notably, the combination of Capsaicin with amoxicillin exhibited enhanced antimicrobial activity, resulting in a statistically significant reduction in the MIC (P < 0.05) and MBC (P < 0.01) compared to each agent alone. Conclusion: The combination of Capsaicin with amoxicillin demonstrated enhanced bactericidal efficacy in a dosedependent manner. Notably, Capsaicin exhibited bactericidal activity at microgram concentrations, whereas amoxicillin required milligram concentrations to achieve a comparable effect, highlighting the potent antibacterial properties of Capsaicin. These findings suggest that both the aqueous extract of C. annuum L. and Capsaicin hold significant potential as promising candidates for the development of novel antimicrobial therapies against S. pyogenes.